2023
DOI: 10.17159/sajs.2023/11657
|View full text |Cite
|
Sign up to set email alerts
|

Current situation and future prognosis of health, safety and environment risk assessment of nanomaterials in South Africa

Abstract: The commercialisation and everyday use of nanomaterials and nanomaterial-enabled products (NEPs) is rising year-on-year. Responsible development of nanotechnology includes understanding their potential implications on health, safety, and the environment (HSE). The health risk assessment of nanomaterials has therefore become one of the major activities of international agencies including the Organisation for Economic Co-operation and Development and the Environmental Protection Agency for protection of human he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The evaluation assay on the applications of nanomaterials is crucial for a longer life. Gulumian et al [ 124 ] reported the current risk evaluation of nanomaterials and this research revealed the benefits of organic-type materials to be suitable for various applications.…”
Section: Suitable Npsmentioning
confidence: 99%
“…The evaluation assay on the applications of nanomaterials is crucial for a longer life. Gulumian et al [ 124 ] reported the current risk evaluation of nanomaterials and this research revealed the benefits of organic-type materials to be suitable for various applications.…”
Section: Suitable Npsmentioning
confidence: 99%